PENGARUH RASIO NASI DAN DAGING TERHADAP TOTAL ASAM, PH, DAN SIFAT ORGANOLEPTIK BEKASAM DAGING SAPI - Gita Lispi Marlena; Urip Santoso; Suharyanto suharyanto (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
This study aimed to know the effect of rice and meat ratio on the total acid, pH, and organoleptic properties of beef bekasam. The study employed 5 treatments with 4 replications, namely, 30% rice and 70% meat (P1), 40% rice and 60% meat (P2), 50% rice and 50% meat (P2). P3), 60% rice and 40% meat (P4), 70% rice and 30% meat (P5). The variables observed were cooking loss, pH, total acid, moisture content and organoleptic properties. The data were analysed for variance (ANOVA) and post hoc DMNRT. The results showed that the ratio of rice and meat had a significant effect (P<0.05) on cooking loss, pH, total acid and organoleptic properties of beef bekasam, but had no significant effect (P>0.05) on moisture content. So it could be concluded that the ratio of rice and meat in the manufacture of beef bekasam had an effect on cooking loss, pH and total acid but has no effect on the water content of beef bekasam. The use of a ratio of 30% rice and 70% meat showed the bekasam with the best physical characteristics and the most prefered by panelists. Keywords: Bekasam, organoleptics, pH, total acids.